SOSIALISASI DAN PELATIHAN APLIKASI GOBIZ MERCHANT UNTUK MEMPERMUDAH PENJUALAN ONLINE BAGI UMKM DAN ANGGOTA KOPERASI AKRAB KELURAHAN PONDOK MELATI, KOTA BEKASI - Ahmad Nurdin Hasibuan; Kamarul Zaman Rambe; Widad Widad; Syamsul Bachri; Harisman Harisman (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2023)
Implementation of Socialization and Training on the GoBiz Merchant Application to facilitate online sales for MSMEs and members of the AKRAB Cooperative, Pondok Melati Village, Bekasi City. This activity was organized by the Community Service Team of the 1957 Kosgoro Institute of Business and Informatics for businesses to be able to take advantage of online business and provide input to the wider community and especially members of the Akrab Cooperative and UMKM Pondok Melati Village, Bekasi City. The implementation of socialization and training was completed with good results, as evidenced by the large number and enthusiasm of participants to follow and understand and use the GoBiz application, a concept that is increasingly attractive to cooperatives and MSMEs. This concept is very important for cooperatives and SMEs for a simple reason that has long been known, namely the change in consumer behavior from traditional shops to online shops. From the MSME and Cooperative perspective, limited knowledge and ability to use online applications and resources encourage cooperatives and UKM to seek new ways to meet consumer needs and wants. The GoBiz application is an option that traders can use in their buying and selling activities using current information technology.